Impact of the COVID-19 pandemic on infectious disease treatment and infection control in Japan: A retrospective multicenter study - Shigeki Kakuno; Waki Imoto; Koichi Yamada; Yasutaka Ihara; Kayoko Yamada; Makoto Tanaka; Gaku Kuwabara; Kana Sawa; Tsuneko Terachi; Tetsu Mizutani; Miyoshi Kitazato; Mayumi Yoshimura; et al. (Heliyon, 2025)
Objectives: The COVID-19 pandemic affected infection control practices such as hand hygiene and antimicrobial use in hospital settings; however, its specific effects on hospital infection control remain unclear. This study aimed to determine the effect of the COVID-19 pandemic on infection control practices. Methods: This retrospective study was conducted at four Japanese hospitals. Data on hand sanitizer use, antimicrobial use, positive blood cultures, and detection of multidrug-resistant organisms (MDRO) were collected monthly from April 2015 to March 2023. The pre-COVID-19 period (April 2015 to March 2020) was compared with the COVID-19 period (April 2020 to March 2023). Results: Hand sanitizer use per inpatient and antimicrobial use, particularly broad-spectrum antimicrobial use, increased significantly during the COVID-19 period. The number of positive blood cultures increased, whereas the number of MDRO infections remained unchanged, suggesting increased contamination. Conclusions: Increased hand hygiene during COVID-19 did not reduce MDRO infections, possibly due to improper technique or timing. Increases in broad-spectrum antimicrobial prescriptions may have contributed to the lack of reduction in MDRO infections. Ongoing antimicrobial use monitoring, hand hygiene education, and promotion of effective infection control and antimicrobial stewardship by infection control teams are crucial for maintaining infection control during epidemics.